TABARRU'S FUNDS AND INVESTMENT INCOME ON ASSET GROWTH IN SHARIA GENERAL INSURANCE COMPANIES - Fatimah, Fatimah; Darmawansyah, Trisna Taufik; Humaemah, Queen; Aguspriyani, Yani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The development of sharia insurance in Indonesia is still relatively small compared to conventional insurance. At the end of 2022, traditional insurance premiums will hold a market share of 50.32%, followed by social and mandatory insurance premiums at 45%, while sharia insurance premiums contribute 4.76%. For this reason, increasing company assets can expand the Sharia insurance company's business and make it more expansive. Some factors can cause assets to grow, including tabarru funds and investment income. The problem formulation in this research is: 1). How do Tabarru's funds influence asset growth in Sharia general insurance registered with AASI? 2). How does investment income affect asset growth in Sharia general insurance companies registered with AASI? 3). Do Tabarru's funds and investment income affect asset growth in Sharia general insurance companies registered with AASI? This research uses quantitative methods. The population in this study was comprised of Sharia general insurance companies registered with AASI, namely 25 companies. The samples taken were six companies using the purposive sampling method . The data analysis method used is panel data regression using Eviews 12 software. The conclusion of the research results from hypothesis testing is that the Tabrru fund variable partially affects Sharia insurance assets' growth. In contrast, the investment income variable does not affect the growth of Sharia insurance assets. Meanwhile, the variables tabarru' funds and investment income influence the growth of Sharia general insurance company assets with a calculated F value of 11.46701 > F table, namely 3.354130829 and a sig value of 0.000005 < 0.05